Assessment of Calcium, Phosphate and Magnesium Levels among Sudanese Children with Malnutrition Ibrahim Malik Hospital, Khartoum, Sudan - Bushra, Khansa Hassan; Elmahadi, Salih Abdelgadir; Ismail, Ismail Mohamed (Gezira Journal of Health Sciences, 2021)
Background: Malnutrition is currently the most widespread and serious health problem of children in the world. Objective: This study aimed to assess calcium, phosphate and magnesium levels among Sudanese Children with Malnutrition. Materials and Methods: This is a hospital based case control study, which was conducted in the period from 2014 to 2015.A total of 120 samples were collected (60 patients and 60 apparently healthy individuals served as control.Quantitative method by mindary BS200 was used to estimate calcium, phosphorus and magnesium levels in Sudanese children with malnutrition and control group. Data was analyzed using SPSS version 25. Results: The results showed that 31 (52%) of patients were males and 29 (48%) were females. Thirty seven 37(62%) of malnourished children had Marasmus, 15(25%) of them had Kwash and 8(13%) had marasmic kwash. Forty four 44(73%) of the malnourished children were less than 12 month while 16(27%) were more than 12 month.Mean of BMI, calcium, phosphate and magnesium in patients and control groups when compared showed a significantly decreased in malnourished children as BMI (12.25±0.91 versus 14.71±0.76) calcium (5.59±0.98 versus 9.19±0.62) phosphorus (2.81±0.45 versus 5.26±2.3) magnesium (1.01±0.24 versus 1.91±0.18) P-values 0.006, 0.000, 0.000 and 0.000 respectively. Plasma calcium and magnesium levels in males did not reveal significant change versus female group whereas phosphate element significantly decreased among females, p.value 0.038. There was positive correlation between BMI,Calcium and Phosphorous levels (R=0.269, P=0.038 and (R=0.258, P=0.044) while there was no correlation between BMI and magnesium level (R=0.074, P=0.572). Conclusion : This study concluded that, calcium, phosphorous and magnesium levels were reduced in malnutrition children patients, and phosphate element decreased among female group rather than male.